The Effects of Rhythm on Building Openings and Fenestrations on Airflow Pattern in Tropical Low-Rise Residential Buildings - Peter I. Oforji; Emeka J. Mba; Francis O. Okeke (Civil Engineering Journal, 2023)
Effective passive airflow in low-rise residential buildings in hot-humid environment is crucial to maintaining good indoor thermal comfort for occupants. However, investigation of effects of the rhythm of window openings on achieving a passive airflow pattern in such buildings in the tropical climate of sub-Saharan Nigeria have been rarely studied. Therefore, this research aimed to evaluate the effects of the rhythm of window openings on passive airflow patterns for indoor thermal comfort in low-rise residential buildings in the hot-humid environment of Obosi, Nigeria. It involved experimental research using the Anemometer TA465 instrument for measuring wind velocity, relative humidity, and temperature of the purposively designated buildings in the three layouts of the study area for both wet and dry seasons. Employing the Yamane statistical formula, a sample size of 433 was obtained, and questionnaires were administered to occupants of the studied buildings and analyzed using categorical Regression Analysis (CATREG). The regression analysis showed that p=0.000, i.e. p<0.05 indicating that there was a significant relationship between the type and sizes of windows (elements used in measuring rhythm) and the intensity or force of breeze (a measure of passive airflow pattern). Further analysis of the data involved the use of Autodesk CFD 2018 (Computational Fluid Dynamics) for building wind flow simulations. The result showed variations in temperature levels (indications of differences in indoor thermal comfort) of various indoor spaces of the investigated designated floors and buildings, especially ground floors and the top-most floors of the buildings. The study underscored the need to use architectural rhythm design strategies to create a positive impact on airflow patterns in low-rise buildings, especially in densely built-up urban areas. The results of this study are instructive in noting that in order to attain passive airflow in buildings in the face of challenge of land restrictions, vertical stacking of building floors could be used once an adequate rhythm of window openings is adopted.Â Doi: 10.28991/CEJ-2023-09-08-016 Full Text: PDF